PENGARUH PENGETAHUAN PAJAK, TINGKAT PENDAPATAN, DAN SOSIALISASI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KOTA BEKASI - Kayla Faritza Hani; Suhono Suhono; Angga Sanita Putra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
Motor vehicle taxpayer compliance is an important factor in increasing regional tax revenue. However, the level of motor vehicle taxpayer compliance in Bekasi City still faces various challenges influenced by both internal and external factors. This study aims to analyze the effect of tax knowledge, income level, and tax socialization on motor vehicle taxpayer compliance in Bekasi City. This research employed a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to 400 motor vehicle taxpayers registered at the Bekasi City SAMSAT Office using a five-point Likert scale. Data analysis techniques included validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, coefficient of determination (R²), F-test, and t-test. The results indicate that tax knowledge has a positive and significant effect on motor vehicle taxpayer compliance with a coefficient value of 0.251 and a significance level of <0.001. Income level has a positive and significant effect on motor vehicle taxpayer compliance with a coefficient value of 0.305 and a significance level of <0.001. Tax socialization also has a positive and significant effect on motor vehicle taxpayer compliance with a coefficient value of 0.287 and a significance level of <0.001. Simultaneously, tax knowledge, income level, and tax socialization significantly affect motor vehicle taxpayer compliance with a significance level of <0.001 and explain 52.3% of the variation in taxpayer compliance. These findings indicate that improving tax knowledge, income level, and tax socialization can enhance motor vehicle taxpayer compliance in Bekasi City.